2012
DOI: 10.1007/s12262-012-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Trauma Care in India: the Potential Role of the Rural Trauma Team Development Course (RTTDC)

Abstract: The Rural Trauma Team Development Course (RTTDC) was devised to optimize trauma resuscitation training in under-resourced rural institutions. This program appears ideal for India because of its dense traffic, large population, and high frequency of rural trauma. We report on the feasibility and desirability of introducing RTTDC in India. An instructor course for 20 faculties and a provider course for 23 were conducted in New Delhi, India. The courses were evaluated by multiple choice question (MCQ) performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
(9 reference statements)
2
13
0
Order By: Relevance
“…The efficacy of course content was evaluated using a five-point Likert scale for feedback from participants. 14,15 In a previous study on the efficacy of the content of the RTTDC course, more than 94% of participants strongly agreed or agreed that the course content had a positive impact on them. 15 In a study on RTTDC course, 100% of participants who were training to be RTTDC providers and 80%e95% participants training to be RTTDC instructors perceived that course content was highly effective.…”
Section: Comparison With Other Courses and Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…The efficacy of course content was evaluated using a five-point Likert scale for feedback from participants. 14,15 In a previous study on the efficacy of the content of the RTTDC course, more than 94% of participants strongly agreed or agreed that the course content had a positive impact on them. 15 In a study on RTTDC course, 100% of participants who were training to be RTTDC providers and 80%e95% participants training to be RTTDC instructors perceived that course content was highly effective.…”
Section: Comparison With Other Courses and Studiesmentioning
confidence: 97%
“…15 In a study on RTTDC course, 100% of participants who were training to be RTTDC providers and 80%e95% participants training to be RTTDC instructors perceived that course content was highly effective. 14 In another study (16), 100% of participants perceived that the course objectives were achieved by the content of the TEAM course. In the present study, 84.7%e86.5% of participants strongly agreed or agreed that the ATAM course content was effective.…”
Section: Comparison With Other Courses and Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…J Ali et al demonstrated how ATLS course was established in an Indian rural setting [12]. Theteam at AIIMS formulated a ACCC consensus committee consisting of 8 members to develop ACCC course material over 10 months in 2014 by using that infrastructure and expertise.…”
mentioning
confidence: 99%